2020
DOI: 10.1530/erc-19-0448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epigenetic pathway inhibitors on corticotroph tumour AtT20 cells

Abstract: Medical treatments for corticotrophinomas are limited, and we therefore investigated the effects of epigenetic modulators, a new class of anti-tumour drugs, on the murine adrenocorticotropic hormone (ACTH)-secreting corticotrophinoma cell line AtT20. We found that AtT20 cells express members of the bromo and extra-terminal (BET) protein family, which bind acetylated histones, and therefore, studied the anti-proliferative and pro-apoptotic effects of two BET inhibitors, referred to as (+)-JQ1 (JQ1) and PFI-1, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Endocrine-Related Cancer pancreatic, pituitary and bronchial NEN cell lines, as well as reducing ACTH secretion from the ACTH-secreting pituitary cell lines, AtT20 (Lines et al 2017(Lines et al , 2020. Furthermore, in vivo, assessment using a pancreatic β-cellspecific conditional Men1-knockout mouse model that develops pNENs, revealed that JQ1 decreased proliferation and increased apoptosis of pNENs (Lines et al 2017).…”
Section: :9mentioning
confidence: 99%
“…Endocrine-Related Cancer pancreatic, pituitary and bronchial NEN cell lines, as well as reducing ACTH secretion from the ACTH-secreting pituitary cell lines, AtT20 (Lines et al 2017(Lines et al , 2020. Furthermore, in vivo, assessment using a pancreatic β-cellspecific conditional Men1-knockout mouse model that develops pNENs, revealed that JQ1 decreased proliferation and increased apoptosis of pNENs (Lines et al 2017).…”
Section: :9mentioning
confidence: 99%
“…Increasing evidence indicates that aberrant epigenetic modifications play an important role in pituitary tumourigenesis ( Shariq & Lines 2019 ), and previously we have demonstrated that the bromo and extra terminal domain (BET) protein inhibitor, JQ1+, reduces proliferation and increases apoptosis of the corticotroph murine cell line, AtT20 ( Lines et al 2020 ), indicating it may also represent an effective novel therapy for corticotrophinomas. The mechanism by which JQ1+ alters proliferation and apoptosis in these cells is, however, incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which JQ1+ alters proliferation and apoptosis in these cells is, however, incompletely understood. To elucidate the target pathways of JQ1+ in pituitary cells, we previously undertook RNA sequence analysis ( Lines et al 2020 ). This revealed that one of the most highly significantly downregulated genes was the calcium-sensing receptor (CaSR) (Supplementary Table 1, see section on supplementary materials given at the end of this article).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations